2013
DOI: 10.3402/ijch.v72i0.19928
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing and contextualizing food insecurity among Greenlandic children

Abstract: ObjectiveTo review the context of food insecurity in Greenlandic children, to review and compare the outcomes related to food insecurity in Greenlandic children, in other Arctic child populations and in other western societies, and to explore the measure used by the Health Behaviour in School-aged Children (HBSC) study.DesignThe study includes literature reviews, focus group interviews with children and analyses of data from the HBSC study. HBSC is an international cross-national school-based survey on child a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
0
18
1
Order By: Relevance
“…Many of these studies address food insecurity or the nutritional quality of the diet among targeted sections of society (e.g., Melchior et al 2009;Niclasen et al 2013;Tingay et al 2003). Others focus on soup kitchen and other measures to alleviate the problems (Silvasti 2014).…”
Section: Food Insecurity and Risk Groups In Western Parts Of The Worldmentioning
confidence: 98%
“…Many of these studies address food insecurity or the nutritional quality of the diet among targeted sections of society (e.g., Melchior et al 2009;Niclasen et al 2013;Tingay et al 2003). Others focus on soup kitchen and other measures to alleviate the problems (Silvasti 2014).…”
Section: Food Insecurity and Risk Groups In Western Parts Of The Worldmentioning
confidence: 98%
“…Hunger during childhood is related to poor food and nutritional environments in families (Robaina and Martin 2013 ; Alaimo et al 2001 ). It is also prognostic for negative child health outcomes such as obesity (Nackers and Appelhans 2013 ), poor self-rated health (Niclasen et al 2013a , b ), increased physical symptoms and associated medicine use (Niclasen et al 2013a , b ), poorer emotional health (Melchior et al 2012 ), lower health-related quality of life (Casey et al 2005 ), and impaired physical function (Casey et al 2005 ). Hunger associated with poor nutrition also makes children vulnerable to disease due to infections (World Food Programme 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 1 in 16 young people reported that they “often” or “always” went to bed hungry during the summer holiday period. Other international studies have reported relatively higher estimates of food insecurity at around 11% [39,40] although the methods for assessing food insecurity vary widely. In the present study, there was a trend for higher reports among children from poorer families (e.g., 7.2%, 5.8% and 5.1% for those reporting a low, medium and high FAS, respectively).…”
Section: Discussionmentioning
confidence: 99%